2012
DOI: 10.48550/arxiv.1203.4025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hadronic Form Factor Models and Spectroscopy Within the Gauge/Gravity Correspondence

Guy F. de Teramond,
Stanley J. Brodsky

Abstract: We show that the nonperturbative light-front dynamics of relativistic hadronic bound states has a dual semiclassical gravity description on a higher dimensional warped AdS space in the limit of zero quark masses. This mapping of AdS gravity theory to the boundary quantum field theory, quantized at fixed light-front time, allows one to establish a precise relation between holographic wave functions in AdS space and the light-front wavefunctions describing the internal structure of hadrons. The resulting AdS/QCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
124
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(130 citation statements)
references
References 125 publications
(312 reference statements)
4
124
2
Order By: Relevance
“…The Q 2 behavior of the prediction of the QCD sum rule inspired model[16] disagrees strongly with the data. The pQCD prediction of Gousset and Pire[17] is nearly a factor two smaller than our measurements, and the latest AdS/QCD prediction by Brodsky and de Teramond[18] reproduces the data below 5 GeV2 , but falls to 2/3 of the observed values for |Q 2 | > 5 GeV 2 . Czyz et al [19] have shown that the measured F π (|Q 2 |) at |Q 2 | > 5 GeV 2 can be parameterized in a VDM approach, but only by including hypothesized radial ρ 3 , ρ 4 , ρ 5 resonances.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…The Q 2 behavior of the prediction of the QCD sum rule inspired model[16] disagrees strongly with the data. The pQCD prediction of Gousset and Pire[17] is nearly a factor two smaller than our measurements, and the latest AdS/QCD prediction by Brodsky and de Teramond[18] reproduces the data below 5 GeV2 , but falls to 2/3 of the observed values for |Q 2 | > 5 GeV 2 . Czyz et al [19] have shown that the measured F π (|Q 2 |) at |Q 2 | > 5 GeV 2 can be parameterized in a VDM approach, but only by including hypothesized radial ρ 3 , ρ 4 , ρ 5 resonances.…”
contrasting
confidence: 48%
“…The solid points in the pion and proton panels are from BaBar ISR measurements [14,22], the open triangles are from FNAL pp measurements [4], the open circles are from the CLEO measurements [5], the open squares at |Q 2 | = 16.1 GeV 2 and 18.3 GeV 2 are from our small statistics data sets, and the solid squares are from the present measurements at |Q 2 | = 14.2 GeV 2 and 17.4 GeV 2 . The theoretical curves for pions are from References [16,17,18]. The solid curves illustrate the arbitrarily normalized variation of αS for π and K, and α 2 S variation for protons.…”
mentioning
confidence: 99%
“…The result is a relativistic and frame-independent semiclassical wave equation, which predicts a massless pion in the massless quark limit and Regge behavior for hadrons with the same slope in both orbital angular momentum L and the radial quantum number n [15]. The model also predicts hadronic light-front wavefunctions which underlie form factors [16] and other dynamical observables, as well as vector meson electroproduction [17].…”
Section: The Mass Scalementioning
confidence: 81%
“…While according to the AdS/CFT correspondence or AdS/QCD correspondence [5,[11][12][13][14] we know that the holographic duality of entanglement entropy between boundary region A and its complement is the holographic entanglement entropy which can be calculated by the Ryu-Takayanagi formula [15,16] S A ≡ S h A = Area(min m(A)∼A {m(A)})…”
Section: Introductionmentioning
confidence: 99%